Numerical Modeling of Seabed Response to Combined Wave-Current Loading - Zhang, J.; Zhang, Y.; Zhang, C.; Jeng, Dong-Sheng (Journal of Offshore Mechanics and Arctic Engineering, 2013)
In this paper, a numerical model is developed to study the dynamic response of a porous seabed to combined wave-current loadings. While the Reynolds-averaged Navier-Stokes equations with k e turbulence closure scheme and internal wave-maker function are solved for the phenomenon of wave-current interaction, Biot's poro-elastic "u p" model is adopted for the seabed response. After validated by the laboratory measurements, this model is applied for the investigation of the effects of waves and currents on the wave-current induced pore pressures. Furthermore, the effects of currents on maximum liquefaction depths of a porous seabed is examined, and it is concluded that the opposite currents will increase the liquefaction depth up to 30% of that without currents. No Full Text